2021
DOI: 10.1038/s41419-021-04227-0
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin activates the p62–Keap1–Nrf2 signalling pathway to alleviate oxidative stress and excessive autophagy in severe acute pancreatitis-related acute lung injury

Abstract: Acute lung injury (ALI) is a complication of severe acute pancreatitis (SAP). Sitagliptin (SIT) is a DPP4 inhibitor that exerts anti-inflammatory and antioxidant effects; however, its mechanism of action in SAP-ALI remains unclear. In this study, we investigated the effects of SIT on SAP-ALI and the specific pathways involved in SAP-induced lung inflammation, including oxidative stress, autophagy, and p62–Kelch-like ECH-associated protein 1 (Keap1)–NF-E2-related factor 2 (Nrf2) signalling pathways. Nrf2 knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 59 publications
1
63
0
Order By: Relevance
“…Once subjected to the oxidative stress, NRF2 can be transferred to the nucleus and bind to the antioxidant response element (ARE) to induce the transcription of target genes, thereby activating downstream antioxidant proteins, such as hemeoxygenase-1 (HO-1) and NAD(P) H quinone oxidoreductase-1 (NQO1), to defend against oxidative stress [ 34 ]. Sitagliptin has been reported to relieve acute pancreatitis-associated acute lung injury and intestinal inflammation by activating NRF2 [ 7 , 35 ]. Our results showed that administration with Sitagliptin significantly reversed the increase of MDA in intestinal tissues of irradiated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once subjected to the oxidative stress, NRF2 can be transferred to the nucleus and bind to the antioxidant response element (ARE) to induce the transcription of target genes, thereby activating downstream antioxidant proteins, such as hemeoxygenase-1 (HO-1) and NAD(P) H quinone oxidoreductase-1 (NQO1), to defend against oxidative stress [ 34 ]. Sitagliptin has been reported to relieve acute pancreatitis-associated acute lung injury and intestinal inflammation by activating NRF2 [ 7 , 35 ]. Our results showed that administration with Sitagliptin significantly reversed the increase of MDA in intestinal tissues of irradiated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, treatment with Sitagliptin further promoted the activation of the NRF2-HO-1/NQO1 signaling pathway in both irradiated intestinal tissues and HIEC-6 cells. However, although studies have shown that DDP4 is negatively correlated with NRF2 and DDP4 can be upregulated after NRF2 knockout [ 7 ], the specific molecular mechanism of Sitagliptin regulating NRF2 activation still needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…3 C, D). It was previously reported that p38 MAPK signaling pathway was positively involved in cell pyroptosis [ 17 ] and p62 expression was negatively associated with cell autophagy [ 20 , 21 ]. Our further analysis by Western blotting displayed a more phosphorylated p38 MAPK and lower expression of p62 in the lung tissues of KO mice than those in WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, overexpression of Keap1 was shown to repress the nuclear accumulation and transcriptional activity of Nrf2, while the addition of phase II inducers, which could upregulate Nrf2, was able to relieve this repression. One study indicated that Nrf2 knockout may reduce Nrf2 entry into the nucleus and fail to initiate the transcription of downstream molecules, thereby exacerbating inflammation and autophagy in a severe pancreatitis induced acute lung injury model; however, the Frontiers in Molecular Biosciences frontiersin.org expression of Keap1 was higher in Nrf2 −/− mice than in WT mice (Kong et al, 2021). In contrast, the expression of NQO1 and Ho-1 was downregulated after Nrf2 knockout.…”
Section: Discussionmentioning
confidence: 99%